The Effect of Pulsed Radiofrequency Combined with a Transforaminal Epidural Steroid Injection on Chronic Lumbar Radicular Pain: A Randomized Controlled Trial. (6th March 2016) - Munjupong, Sithapan; Tontisirin, Nuj; Finlayson, Roderick J.
Abstract : Background . Pulsed radiofrequency lesioning (PRFL) of the dorsal root ganglion (DRG) can modulate neural pathways and provide prolonged relief of neuropathic pain, with limited evidence for chronic lumbosacral radicular pain (CLRP). Objective . This study compared the effect of PRFL combined with transforaminal epidural steroid injection (TFESI) to TFESI alone on CLRP. Methods . Forty adults with chronic radicular pain of at least six-month duration were randomly allocated to undergo either a PRFL of the affected DRG followed by a TFESI (treatment group) or a TFESI alone (control group). Participants and assessors were blinded to the allocation and outcomes were assessed at 1, 2, 3, and 4 months. Outcomes . Pain intensity (visual analog score, VAS) was the primary outcome and quality of life (QOL) as measured by the SF-36 was a secondary outcome. Results . There was no difference in baseline characteristics between groups. VAS was significantly lower in the treatment group at 2-month and 3-month but not 4-month follow-up. QOL measurements did not differ between groups. Conclusions . PRFL of the lumbosacral DRG combined with TFESI showed a modest advantage over TFESI alone in reducing pain intensity; however, this did not persist beyond the 3-month follow-up. There was no effect on QOL.